The role of information in agricultural technology adoption: Experimental evidence from rice farmers in Uganda - Van Campenhout, Bjorn (University of Chicago Press, 2021)
Optimal decision making among the poor is often hampered by insufficient knowledge, false beliefs or wrong perceptions. This paper investigates the role of information in the decision to use modern inputs and adopt recommended agronomic practices among rice farmers in Uganda. Using field experiments, I tested whether the provision of technical information about the correct use of modern inputs and practices affects adoption of these technologies, and subsequent rice production. In addition, I assessed whether providing information aimed at changing the perception of the expected returns on such intensification investments led to different outcomes.